2021
DOI: 10.2196/27173
|View full text |Cite
|
Sign up to set email alerts
|

Influences on the Uptake of Health and Well-being Apps and Curated App Portals: Think-Aloud and Interview Study

Abstract: Background Health and well-being smartphone apps can provide a cost-effective solution to addressing unhealthy behaviors. The selection of these apps tends to occur in commercial app stores, where thousands of health apps are available. Their uptake is often influenced by popularity indicators. However, these indicators are not necessarily associated with app effectiveness or evidence-based content. Alternative routes to app selection are increasingly available, such as via curated app portals, bu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Our DCE was based on a comprehensive systematic review investigating factors influencing the uptake and engagement with health and well-being smartphone apps [ 28 ] and a qualitative research component that consisted of a think-aloud and interview study to examine further the previously identified factors or attributes [ 29 ]. The importance of qualitative research lies in ensuring inclusion of attributes that are relevant to most participants [ 25 ].…”
Section: Development Of a Dcementioning
confidence: 99%
“…Our DCE was based on a comprehensive systematic review investigating factors influencing the uptake and engagement with health and well-being smartphone apps [ 28 ] and a qualitative research component that consisted of a think-aloud and interview study to examine further the previously identified factors or attributes [ 29 ]. The importance of qualitative research lies in ensuring inclusion of attributes that are relevant to most participants [ 25 ].…”
Section: Development Of a Dcementioning
confidence: 99%
“…A health app platform is meant to guide individuals to suitable health apps; however, in current initiatives, this process is not sufficiently supported [ 32 , 33 ]. Facilitating the selection process for individuals might be the key to higher app downloads.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this study is the first to evaluate the feasibility and acceptability of a health app platform (ie, a platform providing reliable preselected health apps with a personal health budget of €100 (US $107.35) with end user and other stakeholder experiences. However, participants in the study of Szinay et al [ 24 ] also found the concept of a curated health app portal appealing and indicated such a portal can alleviate privacy concerns and increase trust. Another health app platform has been studied, Intellicare, which was aimed at the treatment of anxiety and depression [ 25 - 27 ].…”
Section: Discussionmentioning
confidence: 99%